FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PELAPORAN KEUANGAN UMKM BERKUALITAS (Survei pada UMKM Peternak di Indonesia) - R. Ait Novatiani; Robertus Ary Novianto; Rita Yuniarti; Diana Sari; Nuryaman; Bachtiar Asikin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
The purpose of this research is to analyze the relationship of the factors that influence the quality of MSME financial reporting. The population selected in this study were 116 farmers in Indonesia, while the sampling technique used was simple random sampling so that the research sample was 54 farmers. The results of the study provide evidence of a positive influence on accounting understanding and human resource competence on quality MSME financial reporting. Thus the factors that influence the quality of MSME financial reporting include factors of accounting understanding and human resource competence.